Protocolized screening effectively identifies myocardial recovery following destination therapy left ventricular assist device implantation. Issue 8 (26th March 2022) - Smith, Nathan J.; Collar, Nicholas; Duvvuri, Padmaraj; Miles, Bryan; Wu, Ruizhe; Szabo, Aniko; Gaglianello, Nunzio; Joyce, Lyle D.; Joyce, David L.
Abstract: Background: Myocardial recovery following left ventricular assist device (LVAD) implantation has been of interest in transplant candidates with non‐ischemic cardiomyopathy but is rare. Evidence suggests that a combination of left ventricular unloading and pharmacologic reverse remodeling is beneficial. Recovery in non‐transplant candidates (i.e., destination therapy [DT]) patients is believed to be even rarer. Methods: All DT LVADs between January 1, 2017 and November 23, 2020 were reviewed. All patients were subjected to an institutional protocol consisting of combined pharmacologic remodeling and mechanical unloading with proactive screening for recovery. The primary outcome of interest was the cumulative incidence of myocardial recovery. Baseline characteristics and operative outcomes were compared between recovered and non‐recovered DT patients using non‐parametric tests to identify predictive factors. Results: A total of 49 patients received DT LVADs. Nine patients were identified as myocardial recovery candidates using the protocol screening criteria. Overall, 11 patients underwent formal confirmatory testing for recovery, of which 10 were deemed recovered and underwent LVAD explant, defunctionalization, or transplantation. 37.5% of patients that had a concomitant coronary artery bypass during LVAD implantation achieved recovery. An equal proportion of ischemic and non‐ischemic cardiomyopathy patients achieved recovery. The cumulative incidence of myocardial recovery was 25.1% at 36 months. No factors were identified as being predictive of recovery. Conclusion: Myocardial recovery in DT LVAD patients can be achieved at a higher rate than previously reported. Revascularization at the time of LVAD is safe and may be beneficial. LVAD therapy may not be the final destination in these patients. Abstract :